Health-related quality of life among adults with and without hypertension: A population-based survey using EQ-5D in Shandong, China. Issue 1 (December 2017) - Zhang, Li; Guo, Xiaolei; Zhang, Jiyu; Chen, Xi; Zhou, Chengchao; Ge, Dandan; Qian, Yangyang
Abstract Previous studies have focused on health-related quality of life (HRQoL) in hypertensive individuals, but few studies have attempted to compare HRQoL between hypertensive and normotensive individuals using the EQ-5D in China. Based on a survey of 3509 adults aged 18 + years, we compared HRQoL between hypertensive and normotensive individuals using a chi-square test, t-test and multi-linear regression model. The results indicated that HRQoL in hypertensive individuals was poorer than that of normotensive individuals in all domains of the EQ-5D and its utility index. In addition, education, complications, household income, and family history of HBP were associated with HRQoL among the hypertensive patients. Factors including age, education, household income, health expenditure, place of residence, and family history of high blood pressure (HBP) were found to be associated with HRQoL in normotensive individuals. Interventions targeting at-risk subgroups, such as modifying existing health insurance schemes to improve them for poor individuals, might be helpful to improve HRQoL.